2019
DOI: 10.1152/jn.00006.2019
|View full text |Cite
|
Sign up to set email alerts
|

Hair cell and neural contributions to the cochlear summating potential

Abstract: The cochlear summating potential (SP) to a tone is a baseline shift that persists for the duration of the burst. It is often considered the most enigmatic of cochlear potentials because its magnitude and polarity vary across frequency and level and its origins are uncertain. In this study, we used pharmacology to isolate sources of the SP originating from the gerbil cochlea. Animals either had the full complement of outer and inner hair cells (OHCs and IHCs) and an intact auditory nerve or had systemic treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 78 publications
2
56
0
Order By: Relevance
“…Overall our data suggest that OHCs and IHCs have similar properties, namely, considerable rectification (Pappa et al, 2019) and a corner frequency not exceeding a few kilohertz. Thus, just like in high-frequency IHCs, the receptor potential of high-frequency OHCs is expected to mainly follow the envelope of the waveform that stimulates their hair bundles.…”
Section: Resultsmentioning
confidence: 56%
“…Overall our data suggest that OHCs and IHCs have similar properties, namely, considerable rectification (Pappa et al, 2019) and a corner frequency not exceeding a few kilohertz. Thus, just like in high-frequency IHCs, the receptor potential of high-frequency OHCs is expected to mainly follow the envelope of the waveform that stimulates their hair bundles.…”
Section: Resultsmentioning
confidence: 56%
“…OHCs are the main contributors to the generation of an early evoked response, the cochlear microphonic (CM), a short-latency potential occurring before wave I of the ABRs. It has been shown that CM originates from the mechano-sensitive transduction channels in the stereocilia of both IHCs and OHCs, with a predominance for the OHCs due to their greater number, and is produced by the opening and closing of transduction channels in the hair bundle that follow the movement of the basilar membrane [144,145]. The CM is an electrophysiological response that is polarity dependent.…”
Section: Objective Assessment Of Ansdmentioning
confidence: 99%
“…The origins of SP are more debated and remain unclear, but it is accepted that SP mainly reflects the activity of IHCs [152]. More recently, the effects of ototoxins and neurotoxins in animal models suggested a possible combined receptor and neural origin of the SP [144].…”
Section: Objective Assessment Of Ansdmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, using LSFM of the gerbil cochlea, we demonstrate that the cochlea's three-dimensional frequency structure can be preserved, displayed, and measured. These measures are of great interest to physiologists investigating the cellular origins of the complex waveforms generated by the cochlea in response to acoustic (e.g., Forgues et al, 2014;Pappa et al, 2019) or electrical (e.g., Li, Lu, Zhang, Hansen, & Li, 2020;Wiegner, Wright, & Vollmer, 2016) stimuli, for monitoring changes in intracochlear pressure levels at defined frequency locations (e.g., Kale & Olson, 2015) F I G U R E 1 8 Application of the three-dimensional frequency map for geometry based physiological investigations. Frequency maps from otic capsule intact specimens retain relationships with external structures, as viewed from the apex (a) or laterally (b).…”
Section: Uses Of Three-dimensional Cochlear Imagesmentioning
confidence: 99%